IMPLEMENTASI HUKUM POSITIF TERHADAP PENETAPAN WASIAT WAJIBAH BERDASARKAN KEWENANGAN HAKIM PENGADILAN AGAMA - Amiroel Oemara Syarief; MERINA PRATIWI (JURNAL HUKUM DAS SOLLEN, 2021)
This study aims to provide guidance to religious court judges with their authority in deciding the heirs who are entitled to a mandatory will. So far, mandatory wills are only given to children and adoptive parents, but in its development, mandatory wills can be given to other parties other than adopted children and adoptive parents, including non-Muslim heirs. The method in this study is a normative juridical method. The results of the study explain that the mandatory will is regulated in the Compilation of Islamic Law where the rules are not clearly regulated by the KHI. To resolve the issue of mandatory wills, judges are authorized by law to resolve cases that enter the judiciary by making legal discoveries of cases that do not yet have permanent legal force, such as by carrying out historical understanding seen in a concrete case in which case the case already has regulations. legally binding, but the regulation must be interpreted in its implementation. Interpretation is tried by studying the origin of the formation of a legal decision, including the origin of its provisions or the origin of the formation of laws. Then it is done by means of a sociological understanding that prioritizes the interests of the purpose of a regulation through a concrete event in the related official regulations. In practice, judges can interpret unclear provisions based on community demands, as well as laws and regulations that are synchronized with social ties and situations that occur. In addition to the two methods used by judges to make legal findings to create laws that are not found in existing regulations, judges can do reasoning or argumentation. The argumentation procedure consists of argumentum per analogium, argumentum a contrario, and legal narrowing.